Retention Systems to Implant-Supported Craniofacial Prostheses - Goiato, Marcelo Coelho [UNESP]; Delben, Juliana Aparecida; Monteiro, Douglas Roberto; Santos, Daniela Micheline dos [UNESP] (Lippincott Williams & Wilkins, 2009)
Osseointegrated implants in craniofacial reconstructions improve prostheses retention and stability and comfort and safety for a patient. According to biomechanical principles, the treatment success regarding osseointegration maintenance depends on an adequate surgical technique associated to a retention system that provides favorable tension distribution to implants. Furthermore, patient expectation, esthetics, function, and anatomic limitations must be evaluated during treatment planning. Therefore, the aims of this study were to present available retention systems to implant-supported craniofacial prosthesis and to highlight the advantages, indications, and limitations. A literature review was conducted through a MEDLINE search. Sixteen articles and 2 textbooks met the inclusion criteria and were included in the review. It was concluded that the success of craniofacial rehabilitation with implants depends on an adequate surgical technique and an adequate selection of a retention system.
Keywords: Maxillofacial prosthesis; osseointegration; retention system